VD_FINDINFO HC / 2018 / 773 vom 31. Oktober 2018 - VD Tribunal cantonal (2018)
BAIL À FERME AGRICOLE, RÉSILIATION, PROLONGATION DU BAIL À FERME | 2 al. 2 CC, 97 al. 1 CO, 16 LBFA, 22 al. 3 LBFA, 27 LBFA